ISOLATION AND ANTAGONISM OF BACTERIA TEST OF BIOTA IN THE MANGROVE ECOSYSTEM KAYU ARA RIVER SIAK REGENCY - Moritania, Rizky; Effendi, Irwan; Feliatra, Feli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
The General area is the mangrove biodiversity and marine life that have biological activity that likely has the same pharmacological potential as an antimicrobial compound. The purpose of this research is to know the bacterial antagonism in isolation from mangrove, mangrove crabs, snails and fish tembakul against pathogenic bacteria (Aeromonas hydrophila, Aeromonas salmonicida, Edwardsiella ictaluri). This research dimula from May – June 2019. From the results of research that has been done shows that isolates that have the capability of antagonism against pathogenic bacteria test three (A. salmonicida, A. hydrophila and E. ictaluri) were isolate CS7 with category stronger, isolate CS6, CS5, CS4, AI4, AI5, CS9 AI2, with weak category, whereas isolates CS1, B22, B33, B44, AI6 AI7 AI8, was only able to inhibit pathogenic test of 2 with a weak category. The results of the DNA analysis of the 16S rRNA sequence with the use and analysis of BLAST obtained that isolates the Bacillus cereus species are included.